OTENTIKASI IMAGE BERBASIS MAGIC SQUARE ORDE n - Kiswara Agung Santoso (UPT Penerbitan Universitas Jember, 2022)
Image is a digital media that is easy to change, so it is susceptible to being used for crime. Image changes may be affected by the unstable internet during transmission or deliberate manipulation of images for specific purposes. Hence, we need a tool to determine the authenticity of the image. One strategy that can be used is to insert code into the entire image, so that any changes to the image information can be detected. The insertion process performed by dividing the image into several blocks, where the size of each block is adjusted according to the size of the magic square order 3. For the authentication process, the image that has been manipulated will be counted for each pixel. The results show that the manipulated image can be detected. The parts of the image that have changed can be identified because the pixel value doesn’t satisfy the magic square rule. Keywords: Authentication, Image, Magic Square, Pixel